HEALTH EDUCATION ON THE IMPORTANCE OF PHYSICAL ACTIVITY FOR ADOLESCENT FEMALE ISLAMIC BOARDING SCHOOL STUDENTS - Firnaliza Rizona; Sukmah Fitriani; Zesi Aprillia; Romy Suwahyu; Zikran Zikran; Luluk Nafisah (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
Adolescents, including female Islamic boarding school students, are an age group that is highly vulnerable to nutritional problems, one of which is caused by low levels of physical activity. Nutritional problems can have long-term consequences if not addressed promptly, including an increased risk of various metabolic diseases later in life. Health education is therefore an important strategy to improve adolescents’ knowledge regarding physical activity. This activity aimed to provide health promotion through video-based education to enhance knowledge about the importance of physical activity. The program was conducted among 30 adolescent female students in an Islamic boarding school located in Ogan Ilir Regency. The intervention consisted of a pre-test and post-test assessing knowledge of physical activity using a structured questionnaire, followed by the main activity, which was a health education session delivered through an educational video. The results showed a significant improvement in knowledge, indicated by an increase in the number of students with good knowledge from 10 students before the intervention to 26 students after the intervention. These findings demonstrate that video-based health education on the importance of physical activity is effective in improving adolescents’ knowledge, particularly among female Islamic boarding school students.